PEMANTAUAN BIBIT HASIL EKSPLORASI PULAU SEMPU DI KEBUN RAYA PURWODADI - Emilia Anjar Prastiwi; Rony Irawanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
Purwodadi Botanic Garden is an ex-situ plant conservation area that has a collection of plants for conservation, research, education, tourism and environmental services. Where the main characteristic of a botanic garden is the availability of documented collections of plants, equipped with seed and herbarium as supporting collections. Purwodadi Botanic Garden has routine activity to carry out exploration as a conservation effort. Exploration and plants collection activities aiming at conservation to save plants from extinction, as well as conducting research and documentation of plant diversity in that area. Sempu Island as a nature reserve has a diversity of ecosystem types and the diversity of flora and fauna that is endemic and unique. In this study aim to find out the plant monitoring of the Sempu Island exploration results that carried out in 2015 and 2016. This is a descriptive study, base on primary data from garden observation and secondary data from registration unit.From the plant exploration results obtained 518 numbers collection with a total number of plant materials were 2207 specimens divided into five teams, each of which amounted of number collection are 163; 111; 120; 112; and 12. From plant monitoring in 2017 and 2018 show that Sempu Island exploration result was planted in Garden 155 number collection. Its means that 45% from exploration become plant collection in Purwodadi Botanic Garden.